The significance of Q-methodology as an innovative method for the investigation of affective variables in second language acquisition - Li, Xiaodong (Frontiers in Psychology, 2022)
Abstract Q methodology has been used in a variety of fields to employ a scientific approach to dealing with subjectivity; yet, its use has just gained momentum in the second language acquisition (SLA) domain recently (Damio, 2016). The present paper argues that Q methodology is remarkably efficient in representing the dynamic quality of complex systems involved in the language learning process, which is, thus, compatible with the complexity and dynamic systems theory (CDST). As Q method enjoys advantages of both qualitative and quantitative lines of research (Irie, 2014), it helps to explore and reflect L2 learners’ subjective views and perceptions about their emotions in an L2 class in a comprehensive manner. With the current growing attention to individuals’ emotional experiences in recent years, SLA research domain is ripe for many scientific inquiries about L2 learners’ affective variables benefiting from this method. The few existing studies in the L2 domain have had interesting findings, which show the Q method should be more extensively used in the field to reveal facts about how learners feel in class from a within-individual point of view. Q method can hopefully be capable of representing the dynamicity and complexity of the affective variables language learners experience in the interactive network of classroom learning. Thus, it is expected that innovative research methods such as the Q method be employed significantly more than before in the dynamic phase of SLA research in the upcoming years.